Pancreas transplantation. Issue 7 (July 2020) - Knight, Simon; Vogel, Thomas; Friend, Peter
Abstract: Pancreas transplantation is now the standard of care for selected patients with diabetes and end-stage renal failure or life-threatening diabetic complications. The morbidity and mortality of pancreas transplantation is higher than other transplant types, and for this reason selection criteria for both donors and recipients are more stringent. Meticulous organ retrieval technique and back-table preparation, and a standard implantation technique using enteric drainage are central to good outcomes. Modern immunosuppression has reduced acute rejection rates and lowered the need for long-term corticosteroids. Results have improved over time and recipients of a simultaneous kidney–pancreas transplant can now expect 5-year transplant survival of around 75%. The addition of a pancreas to a kidney transplant for suitable recipients has clear benefits in both length and quality of life, and there is increasing evidence that pancreatic transplantation can reduce or halt the progression of diabetic nephropathy, neuropathy, retinopathy and cardiovascular disease. In patients with normal renal function, pancreatic islet transplantation offers an alternative with reduced peri-procedural morbidity and mortality, at the expense of lower rates of long-term insulin independence.